Examining Braille Material and its Support in the Academic Process (2023)
This paper intended to analyze whether the library resources available for visually impaired students supported their academic process. In order to examine this issue, surveys and semi-structured interviews were conducted to cover the different perspectives and the familiarity of students with functional diversities, the teachers responsible for them, and the librarians in regard to these materials. Additionally, a document analysis was implemented to count the number of braille resources, classify, and collect data about accessibility and content that this material provides. The preliminary results displayed that the library has a lack of braille books in accordance with the number of blind students from different faculties that the same possesses.  The following article discusses the implications this issue has for the academic process.